2022
DOI: 10.2147/nrr.s376343
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Needle Stick Injuries Among Nurses in Jeddah, Saudi Arabia

Abstract: Needle-stick injuries (NSIs), sharp tools, and other devices that penetrate the skin are considered occupational hazards for health workers. The most dangerous pathogens in the blood are transmitted through contaminated needles. Thus, this study aimed to investigate the prevalence and associated factors related to NSIs among nurses in Jeddah, Saudi Arabia. Patients and Methods: A quantitative cross-sectional descriptive study design was used. A total of 219 nurses working in a hospital in Jeddah, Saudi Arabia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Personal characteristics associated with NSIs among dentists in Taiwan included the practitioner's experience, the number of patients seen each day, recapping needles, knowledge of infectious diseases, and adherence to infection control policies [9] . In order to reduce the occurrences of NSIs, nurse education and institutional support are essential because they can enhance and strengthen training on occupational safety, provide enough protective equipment to avoid NSIs, and enhance the working environment in hospitals [3] Development and application of occupational safety and health policies and programs based on those variables, as well as adequate oversight of their execution, are necessary additional steps to reduce the chance of NSIs occurring All nursing professionals, both new and seasoned, need to take NSI prevention training. All healthcare professionals must receive the greatest infection control training.…”
Section: Results and Discussion And Conclusion Preventionmentioning
confidence: 99%
See 4 more Smart Citations
“…Personal characteristics associated with NSIs among dentists in Taiwan included the practitioner's experience, the number of patients seen each day, recapping needles, knowledge of infectious diseases, and adherence to infection control policies [9] . In order to reduce the occurrences of NSIs, nurse education and institutional support are essential because they can enhance and strengthen training on occupational safety, provide enough protective equipment to avoid NSIs, and enhance the working environment in hospitals [3] Development and application of occupational safety and health policies and programs based on those variables, as well as adequate oversight of their execution, are necessary additional steps to reduce the chance of NSIs occurring All nursing professionals, both new and seasoned, need to take NSI prevention training. All healthcare professionals must receive the greatest infection control training.…”
Section: Results and Discussion And Conclusion Preventionmentioning
confidence: 99%
“…Additionally, it was discovered that 60.2% of NSIs were not reported, and that recapping the needles was the source of 41.4% of NSIs. Additionally, their research revealed a connection between working hours, sex, and the occurrence of NSIs [3] .…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations